Development of the Health Disparities Prevention Quality Index for Medicare Accountable Care Organizations - Andrew Anderson; Brigham Walker; Andrea T. Duran; Max Aung; Nurzhan Mukashev; Kevin Callison (Health Equity)
Background: Value-based care aims to improve quality and reduce costs, yet racial and ethnic disparities in health outcomes persist, including within Medicare Shared Savings Program accountable care organizations (ACOs). This study introduces the Health Disparities Prevention Quality Index (HDPQI), a novel measure designed to evaluate disparities in preventable hospital admissions, using heart failure (HF) as a case study. Methods: We analyzed administrative claims for Medicare Fee-for-Service beneficiaries (2018–2019) attributed to 476 ACOs. The HDPQI stratifies preventable HF admissions by race/ethnicity, sex, and dual eligibility, producing subgroup observed-to-expected (O:E) ratios, which are aggregated to generate ACO-level scores. Higher scores indicate more preventable admissions than expected. We used t-tests to compare HDPQI scores and related metrics between higher- and lower-performing ACOs (top and bottom 50%) and assessed sensitivity to varying HF prevalence rates. Results: Higher-performing ACOs (bottom 50%) had an average HDPQI score of 1.13, compared with 1.40 for lower-performing ACOs (top 50%). Lower-performing ACOs exhibited significantly higher total inpatient admissions (1.79 vs. 1.70 per beneficiary, p < 0.001) and greater proportions of HF patients with inpatient admissions (1.46 vs. 1.12, p < 0.001). Subgroup analysis revealed dual-eligible Black females had the highest disparities (O:E ratio = 1.9), while Asian subgroups consistently exhibited lower scores (e.g., Asian males O:E ratio = 0.4). Lower-performing ACOs also showed greater variability in subgroup metrics and higher mean subgroup scores (1.51 vs. 1.26, p < 0.001). Conclusion: The HDPQI provides a granular tool to quantify disparities in preventable HF admissions and identify performance gaps. These results highlight the importance of subgroup-specific strategies to advance equity within ACOs and lay the foundation for validating the HDPQI for broader applications in value-based care.